2009
DOI: 10.1111/j.1365-294x.2009.04291.x
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of vicariance, postglacial dispersal and spawning philopatry: population genetics of the walleyeSander vitreus

Abstract: Population genetic relationships reveal the signatures of current processes such as reproductive behaviour and migration, as well as historic events including vicariance and climate change. We analyse population structure of native walleye Sander vitreus across North America, encompassing 10 nuclear DNA microsatellite loci, 26 spawning sites and 921 samples from watersheds across the Great Lakes, Lake Winnipeg, upper Mississippi River, Ohio River and Mobile Bay of the Gulf Coast. Geographical patterning is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
117
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(146 citation statements)
references
References 92 publications
(127 reference statements)
25
117
4
Order By: Relevance
“…Walleye populations in the SMR expressed a relatively large number of alleles at each microsatellite locus and heterozygosities that were similar to those documented in other populations throughout the midwest by Stepien et al (2009), and in the southeast by Palmer et al (2006). There is no historical genetic baseline to which the current populations in the SMR can be compared, nor historic samples that could be used to generate such a baseline.…”
Section: Walleyesupporting
confidence: 59%
See 1 more Smart Citation
“…Walleye populations in the SMR expressed a relatively large number of alleles at each microsatellite locus and heterozygosities that were similar to those documented in other populations throughout the midwest by Stepien et al (2009), and in the southeast by Palmer et al (2006). There is no historical genetic baseline to which the current populations in the SMR can be compared, nor historic samples that could be used to generate such a baseline.…”
Section: Walleyesupporting
confidence: 59%
“…As population size is reduced, allele frequencies will drift due to a smaller number of breeders, eventually leading to fewer alleles in the population and a decrease in heterozygosity (Cornuet and Luikart, 1996). Microsatellite DNA loci have been used extensively to assess genetic structure of populations (Miller, 2003;Strange and Stepien, 2007;Stepien et al, 2009), and they were chosen as the markers to assess the genetic status and to establish a baseline for future monitoring of the yellow perch and walleye populations in the SMR.…”
Section: Introductionmentioning
confidence: 99%
“…When present, philopatry results in a spatial separation of spawning aggregations across the lake, providing potential for genetic variation to develop over several generations, and for potentially discrete genetic stocks to form within the lake. Genetic work in the Laurentian Great Lakes using both mitochondrial (Stepien and Faber, 1998;Gatt et al, 2002) and nuclear Stepien et al, 2009) DNA variation has revealed genetic differences among walleye spawning sites consistent with those expected from reduced gene flow as a result of philopatry.…”
Section: Introductionmentioning
confidence: 87%
“…This lack of a correlation would occur because there would be no particular reason that close waterheads would be more similar to each other than would waterheads located further apart (e.g., Stepien et al 2009). Although genetic distance will increase with time, there is no reason for time and space to be correlated in this scenario because the processes driving homing behavior are not geographically structured among the subsamples (waterheads).…”
Section: Genetic Comparisons Among Samples From Distinct Waterheadsmentioning
confidence: 94%
“…The absence of spatial patterns will be predicted to occur appear only in the absence of a long-term history of differentiation in the species as well as the presence of a stable migration system (i.e., the waterheads and main river course), geographically independent waterheads and a low ''failure'' of individual homing behavior. Although examples of these assumptions are hard to find in nature, this prediction leads to a different but interesting challenge: the identification of a significant spatial pattern among waterheads will require an additional explanation for the structure of the population beyond that strictly involving homing behavior (see Beheregaray and Sunnucks 2001;Stepien et al 2009). Thus, ironically, the existence of Fig.…”
Section: Genetic Comparisons Among Samples From Distinct Waterheadsmentioning
confidence: 97%